ZnO, TiO2 and Ag nanoparticles impact against some species of pathogenic bacteria and yeast - Mohammed, Asmmaa Khalis; Salh, Khonaw Kader; Ali, Fattma A. (Cellular and Molecular Biology, 2021)
The economic approaches for manufacturing the nanoparticles with physical and chemical effects and limited resistance to antibiotics have been progressed recently due to the rise of microbial resistance to antibiotics. This research aimed to study the antimicrobial efficacy of silver nanoparticles Ag, ZnO, and Tio2 nanoparticles against Salmonella typhimurium and Brucella abortus and Candida albicans. Two isolates of Salmonella and two isolates of Brucella abortus were isolated from food spastically meat and blood specimens, respectively. Candida albicans were isolated from the patient’s mouth with oral candidiasis (oral thrush) and confirmed diagnosis by API 20C test. The antimicrobial susceptibility of Salmonella typhimurium and B. abortus isolates were performed against nine different antibiotics. Silver nanoparticles consisting of AgNPs size (90) nm, ZnO NPs size (20, 50) nm as well as TiO2 NPs size (10, 50) nm, were used. UV-Visible spectrophotometer was used to characterize silver nanoparticles. The highest resistance of Candida albicans was seen for fluconazole, Clotrimazole and Itraconazole. The results of the Minimum Inhibitory Concentration (MIC) of nanoparticles against Salmonella typhimurium showed the average MIC of Tio2-10nm and Tio2-50nm were 5000 and 2500 μgfor S1 and S2 isolates, respectively. The isolated Brucella abortus (B1 and B2) showed sensitivity to NPs with different MIC. The average MIC for Ag-90nm was 5000 and 2500 µg/ml for B1 and B2 isolates, respectively. The findings suggest NP solution has fungicidal and bactericidal impacts on the tested microorganisms so they can be suitable for multiple applications of the biomedical field such as developing new antimicrobial agents.